Handbook of optoelectronics - Dakin, John P 1947-; Brown, Robert G. W. (Taylor & Francis, 2006)
Describes diverse range of research areas within optoelectronics. This book includes basic physics, materials science, and engineering background. It is suitable for designers and researchers of optoelectronic systems and devices in universities, government laboratories, and industry.